2012
DOI: 10.1245/s10434-012-2705-8
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Outcomes after Laparoscopic and Open Hepatectomy for Hepatocellular Carcinoma: A Global Systematic Review and Meta-analysis

Abstract: In patients with solitary left lateral lobe/right peripheral subcapsular tumors treated with minor resection, this meta-analysis demonstrated that compared to OH, LH may have short-term advantages in terms of blood loss and postoperative morbidity for HCC. Both procedures have similar long-term outcomes. It may be time to consider changing the standard procedures for treatment of HCC in the left lateral lobe and peripheral subcapsular right segments in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 47 publications
8
125
2
1
Order By: Relevance
“…described the utility of LLR for HCC. A later systematic review and meta‐analysis of LLR and open liver resection (OLR) showed no significant difference in surgical curability, but LLR was associated with less invasive than OLR 80, 81, 82. These reports are considered the main evidence supporting the utility of LLR in the setting of HCC, because it is unrealistic to conduct a randomized controlled trial comparing the outcomes of OLR and LLR.…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…described the utility of LLR for HCC. A later systematic review and meta‐analysis of LLR and open liver resection (OLR) showed no significant difference in surgical curability, but LLR was associated with less invasive than OLR 80, 81, 82. These reports are considered the main evidence supporting the utility of LLR in the setting of HCC, because it is unrealistic to conduct a randomized controlled trial comparing the outcomes of OLR and LLR.…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…Furthermore, these were found to be lower after LLR in 40 and 11 studies, respectively. Twelve meta-analyses and one Cochrane report were also analyzed [35][36][37][38][39][40][41][42][43][44][45][46][47] and consistent results included reduced blood loss and transfusions requirements when studied. This clearly shows that, in selected patients LLR when compared with open surgery is associated with reduced blood loss and subsequent transfusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Yin et al (76) found that the postoperative morbidity rate after laparoscopic resection of HCC decreased significantly in comparison to open surgery. A meta-analysis indicated that laparoscopic resection consistently yields favorable results in terms of the duration of hospitalization (77)(78)(79), consequently reducing the overall morbidity rate and incidence of intractable ascites.…”
Section: Indications For and The Current Role Of Laparoscopymentioning
confidence: 99%